An empirical examination of the costs and benefits of executive stock options: Evidence from Japan - Kato, Hideaki Kiyoshi; Lemmon, Michael; Luo, Mi; Schallheim, James (Journal of Financial Economics, 2005)
In May 1997, the Japanese Commercial Code was amended to allow firms to begin granting stock options as compensation to top management and employees. Nearly 350 firms adopted option-based compensation plans between 1997 and 2001. These options typically have five-year lives and are out-of-the-money by about 5% at the grant date. Firms exhibit abnormal stock returns of about 2% around the announcements of plan adoptions. We find improvements in operating performance and observe that dividend policy and volatility remain unchanged post-adoption. Our evidence suggests that well-designed incentive compensation plans are consistent with the creation of shareholder value.